1990
DOI: 10.1111/j.1365-2826.1990.tb00645.x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Opiate Peptides with Dopamine Effects on Prolactin Secretion and Membrane Electrical Properties in Anterior Pituitary Cells from Lactating Rats

Abstract: Met-enkephalin and b-endorphin induced a partial reversion of the dopamine inhibition of prolactin release from pituitary cells of lactating rats in primary culture. This effect of opiate peptides was dose-dependent with an EC50 of 40f8 nM and 4 5 + 7 nM and maximal blockade of dopamine inhibition of 60% and 68% for Met-enkephalin and /]-endorphin, respectively. Naloxone antagonized the effect of Met-enkephalin with an EC50 of 22_$12 nM. Furthermore, this Met-enkephalin effect on dopamine inhibition of prolact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Previous studies have reported a change in the characteristics of these neurons in lactating rodents, with detection of increased opioidergic immunoreactivity in the arcuate nucleus [131,132] and specific expression of enkephalin (Enk) in TIDA neurons. Positive effects of endogenous opioids on PRL secretion have been described [133], which could result from inhibition of TIDA neurons themselves via suppression of DA turnover [134] or TH activity [135]. Thus, a role for Enk may be to reinforce the suppression of DA secretion from TIDA neurons, although as there are numerous other targets for opioids within the hypothalamus, as well as other regions of the brain [136], it is tempting to speculate that Enk may instead modify secretion of potential PRL-releasing factors.…”
Section: The Opioid Switch?mentioning
confidence: 99%
“…Previous studies have reported a change in the characteristics of these neurons in lactating rodents, with detection of increased opioidergic immunoreactivity in the arcuate nucleus [131,132] and specific expression of enkephalin (Enk) in TIDA neurons. Positive effects of endogenous opioids on PRL secretion have been described [133], which could result from inhibition of TIDA neurons themselves via suppression of DA turnover [134] or TH activity [135]. Thus, a role for Enk may be to reinforce the suppression of DA secretion from TIDA neurons, although as there are numerous other targets for opioids within the hypothalamus, as well as other regions of the brain [136], it is tempting to speculate that Enk may instead modify secretion of potential PRL-releasing factors.…”
Section: The Opioid Switch?mentioning
confidence: 99%